"All One Life": Celebrity and Intimacy in the Photographs of Annie Leibovitz. (2nd September 2017) - Zuromskis, Catherine
Abstract: Few photographers are as well known or as representative of American celebrity culture in the contemporary media age as Annie Leibovitz. This essay analyzes Leibovitz's influential style by situating it within the complexities of both celebrity and snapshot photography. Taking as its jumping off point Leibovitz's2006 retrospective, A Photographer's Life, which pairs the photographer's iconic celebrity portraits with dramatically personal photographs of her family, friends, and lover Susan Sontag, it examines the interrelations between celebrity artifice and interpersonal intimacy intimated by Leibovitz's claim that together, her photographs represent "one life." This essay offers an analysis of key shifts and contradictions in Leibovitz's work: the evolution from the gritty realist style of her early Rolling Stone work to the highly manufactured "conceptual" work that characterizes her Portraits campaign for American Express and her more recent work for Vanity Fair, and the contradiction between Leibovitz's iconoclast reputation and the surprisingly normative politics it supports. Yet despite these contradictions, it argues, there is a coherence in Leibovitz's work in its reliance on manufactured intimacies. In both her personal and her professional work, Leibovitz offers a visceral, sensational image experience, but one that tells us little we didn't already know.